PERTUMBUHAN EKSPOR KOMODITAS BAWANG MERAH DI KABUPATEN BREBES 2014-2018 - Mukhroji; Widyantoro, Sigid (El-Hamra, 2020)
The export growth of shallot, especially from Brebes Regency not stable yet. It happened cause by the competition from the like products entering Indonesian market and the fluctuation of the market price. The purpose of this research was to (a)analyzing shallots as local prime commodity, (b)analyzing the dynamic and problematic of shallots commodity in domestic and export market, (c)analyzing the opportunities to increase the export of the shallot’s commodity. The method used in this research was qualitative method with SWOT (Strengths, Opportunities, Weaknesses, Threats) analysis as a method used to determine the strategy from the Strengths, Opportunities, Weaknesses, Threats in the export’s growth of shallots. Key Words: shallot, export, commodity, swot analysis